Sistem Informasi Monitoring Implementasi Bantuan Dana Sosial Peningkatan UMKM Masyarakat Binaan Dinas Sosial - Winda Sari Depi Simamora (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
Micro, Small and Medium Enterprises (MSMEs) in the Social Service of the North Sumatra Province Batubara Regency are business operators engaged in the business sector, which touches the interests of the community around the Regency of Coal. MSMEs have an important position, not only in employment and public welfare, in many ways they are the glue and stabilize the problem of social inequality. MSMEs are currently very developed. However, the current problem that arises is that the Chair of the UMKM in Coal is having difficulty monitoring MSME social funding assistance provided to communities around Coal, the lack of public understanding of the reporting of the social assistance fund accountability and due to these inaccessible location conditions that triggered the social services difficult to monitor. then we need an information system that is able to do data collection, management, monitoring the use of aid funds. In addition, the Social Service can directly monitor the responsibility of MSMEs in managing aid funds.The results of this study are a monitoring information system application that replaces the previously running process, in this application makes it easy for the recipient to know the amount of assistance received and in making reports can be directly accessed online.